Examining The Pilgrims’ Experience: Communitas Along The Camino De Santiago - Brumec, Snežana (The international journal of religious tourism and pilgrimage, 2023)
To what extent does the community formed among pilgrims on the Camino de Santiago correspond to Turner’s concept of communitas? How might pilgrimage with significant others differ from individual pilgrimages in the sense of community? This study attempts to answer these questions based on qualitative and quantitative content analysis of 32 travelogues written by pilgrims who completed the pilgrimage alone or with relatives or friends. The findings show that pilgrims develop an egalitarian and creative community that prevails the notion of a generic bond between people, an intense comradeship and generous common friendliness. In such a community, pilgrims’ behaviour is typically passive or humble, and wisdom has ontological value. Pilgrims have similar experiences of communitas regardless of going to Santiago alone or with significant others. However, pilgrims who join organised groups solely for the last 100 kilometres of their journey are not considered part of this community and are classified as pseudo-pilgrims.